2019
DOI: 10.1038/s41698-019-0100-7
|View full text |Cite
|
Sign up to set email alerts
|

Germline variants associated with leukocyte genes predict tumor recurrence in breast cancer patients

Abstract: Germline variants such as BRCA1/2 play an important role in tumorigenesis and clinical outcomes of cancer patients. However, only a small fraction (i.e., 5–10%) of inherited variants has been associated with clinical outcomes (e.g., BRCA1/2, APC, TP53, PTEN and so on). The challenge remains in using these inherited germline variants to predict clinical outcomes of cancer patient population. In an attempt to solve this issue, we applied our recently developed algorithm, eTumorMetastasis, which constructs predic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…Germline variants influence clinic outcomes of complex disease. Recent studies found that functionally mutations of natural killer cells were positively associated with cancer risk [7,8]. Similarly, in our previous study found that the KATP SNP rs1799858 was associated with increased risk of elevated LDL-C serum concentration (≥ 1.8 mmol/L) and its related macro-/micro-vascular arteriosclerotic events.…”
Section: Discussionsupporting
confidence: 68%
“…Germline variants influence clinic outcomes of complex disease. Recent studies found that functionally mutations of natural killer cells were positively associated with cancer risk [7,8]. Similarly, in our previous study found that the KATP SNP rs1799858 was associated with increased risk of elevated LDL-C serum concentration (≥ 1.8 mmol/L) and its related macro-/micro-vascular arteriosclerotic events.…”
Section: Discussionsupporting
confidence: 68%
“…21,22 Further, germline mutations can also predict tumor recurrence in breast cancer patients. 38 In the present study, we used ceRNA to detect and validate potential prognostic lncRNAs in the luminal BC.…”
Section: Discussionmentioning
confidence: 99%
“…Besides somatic mutation signatures, germline variants could also be associated with tumor prognosis. Recently, Milanese et al reported different germline variants in recurred and non-recurred patients of breast cancers ( Milanese et al, 2019 ). These signature germline variants could potentially facilitate the formation of the pro-tumorigenic environment by impairing adaptive and innate immune pathways and could be used for prediction of breast cancer outcomes ( Milanese et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Milanese et al reported different germline variants in recurred and non-recurred patients of breast cancers ( Milanese et al, 2019 ). These signature germline variants could potentially facilitate the formation of the pro-tumorigenic environment by impairing adaptive and innate immune pathways and could be used for prediction of breast cancer outcomes ( Milanese et al, 2019 ). In another study, Xu et al (2019) observed negative associations between the number of germline defective genes in natural killer cells and survival time in a variety of cancer types.…”
Section: Discussionmentioning
confidence: 99%